Mentoring Program on Solar Power Plant Design for PKBM Ingin Maju Community in Bantaeng - Haripuddin; Al Imran; Sari, Dessy Ana Laila; Zulhajji; Muliaty Yantahin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Based on (Aulia Ryza Aqilla, 2024) previous statement, utilizing renewable energy sources has been increasingly recognized as a trend, this particularly concerning the economic issues faced by the Indonesian population. A green economy involves the adoption of more environmentally friendly energy sources to support citizen’s livelihood. Several areas in Indonesia have begun implementing renewable energy technology, such as solar energy (PLTS), to enhance the life quality for their citizen. PKBM Ingin Maju has become a partner embraced in this program to enhance their knowledge and awareness among the community about transitioning to renewable energy through the planning and implementation of small-scale solar power plant (PLTS). The mentoring activities include presentations on the role and benefits of renewable energy as an alternative to commercial energy sources, which still far short of meeting resident’s energy needs. At the end of the community service program, evaluation showed that most participants were previously unaware of this technology and expressed their willingness to start implementing PLTS at their households.